Revisit the Curriculum Components for the Preparation of Health Services Managers - Saadun, S.; Lewis, Jan (Elsevler, 2014)
This paper is to revisit a curriculum component of health services management (HSM) at universities in Australia that can be used as reference for working with universities to develop their curriculum. The peer reviewed publications, with an emphasis on articles reporting research were identified. The findings set out exactly the most curriculums offered. Further research need to be conducted in other countries offered the similar program and the correlation will be reported on at a later date. The findings can be used to explain the concept of health services management to those new to the subject, and particularly to universities and health services managers to be. This paper seeks to fill the gap between in-depth, scholarly and complex articles about HSM and very simple descriptive articles.